2015
DOI: 10.1177/0956462415580887
|View full text |Cite
|
Sign up to set email alerts
|

Chorioamnionitis in pregnancy: a comparative study of HIV-positive and HIV-negative parturients

Abstract: Background Chorioamnionitis is an important risk factor for vertical transmission of HIV/AIDS. We compared the prevalence and correlates of chorioamnionitis in HIV-positive and HIV-negative pregnant women. Methods HIV-positive and -negative parturients were interviewed, examined and had their placenta examined histologically for chorioamnionitis. Data regarding HIV were also retrieved from their hospital records. Results A total of 298 parturients (150 HIV positive and 148 HIV negative) were enrolled. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Both the inclusion of pre-term deliveries and the more comprehensive microscopic examination would be expected to show a higher prevalence of ACA and thus this might explain why our study showed such, when compared to the previous Ugandan cohort study. Indeed, a recent study that utilized similar diagnostic criteria to ours documented a similarly high prevalence of histologic ACA in both HIV infected (61.6%) and HIV uninfected (57.1%) Nigerian women [24].…”
Section: Discussionmentioning
confidence: 71%
“…Both the inclusion of pre-term deliveries and the more comprehensive microscopic examination would be expected to show a higher prevalence of ACA and thus this might explain why our study showed such, when compared to the previous Ugandan cohort study. Indeed, a recent study that utilized similar diagnostic criteria to ours documented a similarly high prevalence of histologic ACA in both HIV infected (61.6%) and HIV uninfected (57.1%) Nigerian women [24].…”
Section: Discussionmentioning
confidence: 71%
“…Details of the study have been previously published 11 . This cross-sectional study was carried out at the delivery suite of the Jos University Teaching Hospital (JUTH), Plateau State Specialist Hospital, Bingham University Teaching Hospital and Faith Alive Hospital, all in Jos.…”
Section: Study Area and Designmentioning
confidence: 99%
“…infection of fetal membranes and amniotic fluid) is commonly observed in pregnant women with PPROM and may cause neonatal sepsis, preterm birth, pulmonary diseases, and neonatal brain injury. Therefore, early diagnosis of chorioamnionitis is very important (18,19). PCT is a peptide precursor of the calcitonin hormone, which is typically produced by monocytes and hepatocytes (20).…”
Section: Discussionmentioning
confidence: 99%